The stability of graphene and boron nitride for III-nitride epitaxy and post-growth exfoliation. Issue 22 (17th May 2021) - Park, Jeong-Hwan; Yang, Xu; Lee, Jun-Yeob; Park, Mun-Do; Bae, Si-Young; Pristovsek, Markus; Amano, Hiroshi; Lee, Dong-Seon
Abstract : A challenging approach, but one providing a key solution to material growth, remote epitaxy (RE)—a novel concept related to van der Waals epitaxy (vdWE)—requires the stability of a two-dimensional (2-D) material. Abstract : A challenging approach, but one providing a key solution to material growth, remote epitaxy (RE)—a novel concept related to van der Waals epitaxy (vdWE)—requires the stability of a two-dimensional (2-D) material. However, when graphene, a representative 2-D material, is present on substrates that have a nitrogen atom, graphene loss occurs. Although this phenomenon has remained a hurdle for over a decade, restricting the advantages of applying graphene in the growth of III-nitride materials, few previous studies have been conducted. Here, we report the stability of graphene on substrates containing oxygen or nitrogen atoms. Graphene has been observed on highly decomposed Al2 O3 ; however, graphene loss occurred on decomposed AlN at temperatures over 1300 °C. To overcome graphene loss, we investigated 2-D hexagonal boron nitride (h-BN) as an alternative. Unlike graphene on AlN, it was confirmed that h-BN on AlN was intact after the same high-temperature process. Moreover, the overgrown AlN layers on both h-BN/AlN and h-BN/Al2 O3 could be successfully exfoliated, which indicates that 2-D h-BN survived after AlN growth and underlines its availability for the vdWE/RE of III-nitrides with further mechanical transfer. By enhancing the stability of the 2-D material on the substrate, our study provides insights into the realization of a novel epitaxy concept.